232k views
2 votes
Select the two values of x that are roots of this equation.
x + 2x - 6 = 0​

Select the two values of x that are roots of this equation. x + 2x - 6 = 0​-example-1

1 Answer

5 votes

For this case we must solve the following quadratic equation:


x ^ 2 + 2x-6 = 0

Where:


a = 1\\b = 2\\c = -6

The solution is given by:


x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2a}

Substituting:


x = \frac {-2 \pm \sqrt {2 ^ 2-4 (1) (- 6)}} {2 (1)}\\x = \frac {-2 \pm \sqrt {4 + 24}} {2}\\x = \frac {-2 \pm \sqrt {28}} {2}\\x = \frac {-2 \pm \sqrt {2 ^ 2 * 7}} {2}\\x = \frac {-2 \pm2 \sqrt {7}} {2}\\x = -1 \pm \sqrt {7}

Thus, we have two roots:


x_ {1} = - 1+ \sqrt {7}\\x_ {2} = - 1- \sqrt {7}

ANswer:


x_ {1} = - 1+ \sqrt {7}\\x_ {2} = - 1- \sqrt {7}

User CasaDelGato
by
5.8k points